2022
DOI: 10.3389/fpsyg.2022.877277
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Psychosocial Factors of Problematic Smartphone Use Among Chinese College Students: A Three-Wave Longitudinal Study

Abstract: Problematic smartphone use (PSU) in college students has been a major public health concern in modern society, which may also lead to adverse health outcomes. Using a three-wave longitudinal study design, the current study aimed to examine the prevalence and psychosocial factors of PSU in a large sample of Chinese college students. The data used in this study was obtained from an ongoing longitudinal study in Guangdong, China. In the current study, a total of 7,434 freshmen and sophomores who completed the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 58 publications
3
19
1
Order By: Relevance
“…As such, these students may be more susceptible to some of the negative psychological consequences associated with problematic smartphone use, such as anxiety [19,42], depression [9,36,42], and loneliness [14,36]. Importantly, this group contained 22% of the sample, which is in contrast to other recent studies which have found prevalence rates of 52-68% for problematic smartphone use among university students (e.g., [65][66][67]). This discrepancy in findings emphasizes the importance of person-centered work which allows for a more nuanced investigation of the heterogeneity of symptom/feature cooccurrence and thus avoids overpathologizing behaviours which have become largely normative.…”
Section: Discussionmentioning
confidence: 77%
“…As such, these students may be more susceptible to some of the negative psychological consequences associated with problematic smartphone use, such as anxiety [19,42], depression [9,36,42], and loneliness [14,36]. Importantly, this group contained 22% of the sample, which is in contrast to other recent studies which have found prevalence rates of 52-68% for problematic smartphone use among university students (e.g., [65][66][67]). This discrepancy in findings emphasizes the importance of person-centered work which allows for a more nuanced investigation of the heterogeneity of symptom/feature cooccurrence and thus avoids overpathologizing behaviours which have become largely normative.…”
Section: Discussionmentioning
confidence: 77%
“…A few studies have investigated longitudinal associations of PSU. PSU, as measured by SAS-SA has been found to be positively moderately associated with depression and anxiety measured six and eighteen months later among Chinese college students (Wang, Wang, Zhu, & Shi, 2022). Additionally, a medium six-month association between PSU, as measured by the Smartphone Addiction Inventory, and depression has been reported (Zhou, Dang, Lam, Zhang, & Wu, 2021) among Chinese adolescents.…”
Section: Introductionmentioning
confidence: 91%
“…A few studies have investigated the longitudinal associations of PSU. PSU, as measured by the SAS-SV has been found to be moderately positively associated with depression and anxiety measured six and eighteen months later among Chinese college students [ 25 ]. Additionally, a medium six-month association between PSU, as measured by the Smartphone Addiction Inventory, and depression has been reported [ 26 ] among Chinese adolescents.…”
Section: Introductionmentioning
confidence: 99%